Aspirin use is associated with lower indices of liver fibrosis among adults in the United States. Issue 6 (7th January 2016) - Jiang, Z. Gordon; Feldbrügge, L.; Tapper, E. B.; Popov, Y.; Ghaziani, T.; Afdhal, N.; Robson, S. C.; Mukamal, K. J.
Summary: Background: Recent animal studies have shown that platelets directly activate hepatic stellate cells to promote liver fibrosis, whereas anti‐platelet agents decrease liver fibrosis. It is unknown whether platelet inhibition by aspirin prevents liver fibrosis in humans. Aim: To examine the association between aspirin use and liver fibrosis among adults with suspected chronic liver disease. Methods: We conducted a cross‐sectional analysis using data from the National Health and Nutrition Examination Survey III. We identified 1856 individuals with suspected chronic liver disease (CLD). The degree of liver fibrosis was determined using four validated fibrosis indices and a composite index. Results: The use of aspirin was associated with a significantly lower composite liver fibrosis index calculated from FIB4, APRI, Forns and NFS [0.24 standard deviation (s.d.) units lower; 95% CI −0.42 to −0.06, P = 0.009]. The association of aspirin with lower fibrosis scores was significantly larger among those with suspected CLD compared to those without (−0.23 vs. −0.03 s.d. units; P interaction = 0.05). The negative association between aspirin use and lower fibrosis index was consistent across all four fibrosis indices ( P = 0.002–0.08) in individuals with chronic viral hepatitis, suspected alcoholic liver disease and NASH. In comparison, no negative associations with liver fibrosis were seen with ibuprofen in parallel analyses. Conclusions: The use of aspirin was associated with significantly lower indices of liver fibrosis among US adults with suspected chronic liver diseases. Aspirin and other anti‐platelet drugs warrant further investigation for the prevention and treatment of liver fibrosis.